The pattern of carcinoma of the vulva in Zaria, Northern Nigeria - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Background:Cancer of the vulva is a rare gynaecological condition and contributes to about 2.6% of gynaecological malignancies seen in our unit. The prevalence is on the increase and late presentation calls for concern.Objectives:To review the epidemiology of cancer of the vulva within the study period in view of the changing pattern.Methodology:This is a retrospective study of histologically diagnosed vulva cancers seen in our unit between March 2005 and February 2015. The records of the patients were retrieved from our Gynea-oncology register, the Health Management Information Department of the Hospital, cancer registry and the histopathology laboratory. Descriptive statistics were used under excel statistical package to analyse the findings using rates, ratio and proportion.Results:We had a total of 1089 gynaecological malignancies and carcinoma of the vulva accounting for 28 (2.6%) patients. Their ages ranged from 13 to 75 years with a mean of 47 years; parity was 0–14 deliveries with a median of 7 and a mean of 4. Most of the patients were of low socioeconomic class. Eight of the nine patients (88.9%) were managed surgically. Majority of the cases had radical/toilet vulvectomy with inguino-femoral lymphadenectomy and adjuvant radiotherapy because they all presented in the advance stage. The complications included one case of inguinal wound disruption and one case of wound sepsis. There were no deaths. The histological types of cancer of the vulva seen were mainly squamous cell cancer accounting for (22) 78.6%. Others include adenocarcinoma accounted for (3) 10.7%, (2) (7.1%) cases of malignant melanoma and embryonal rhabdomyosarcoma (1) 3.6%.Conclusion:What we see may only be the tip of the iceberg since these old women tend to hide their lesions. The treatment of this disease can be highly successful if only our patients present early and would be able to afford the cost of care.